Seismic attribute analysis of coal seams intruded by magmatic rock. (3rd August 2022) - Chen, Fangbo; Zhu, Jie; Wang, Jiabao; Yang, Yang; Iqbal, Ibrar; Zhang, Tianyu; Li, Ping
Abstract: When magmatic rock intrudes a coal seam, it destroys the coal seam's structure, reduces the coal quality, and brings hidden dangers to the safe production processes of the coal mine. In this study, the mechanism of magmatic rock intrusion into coal seams was briefly described. In addition, the changes in the structure, composition, and geophysics characteristics of the coal seams following the intrusion of magmatic rock were summarized. This study also performed a forward modeling was performed. Then, the effectiveness of the seismic attributes in detecting the ranges of the coal seams intruded by magmatic rocks was theoretically analyzed. It was observed that after the intrusion of magmatic rocks in the coal seams, the seismic attributes were dramatically affected. For example, the frequency band width values increased, central frequency values decreased, and the main amplitude values decreased. For experimental verification purposes, this study selected the test project of the Yuandian coal mine in the Huaibei area of Anhui, China as an example. The accuracy levels for the detection of the ranges of the coal seams intruded by magmatic rock with seismic attributes were successfully verified.